Creating a sense of presence in online teaching : how to "be there" for distance learners - Lehman, Rosemary M., 1932-; Conceicao-Runlee, Simone, 1963- (San Francisco : Jossey-Bass, 2010)
'How can faculty create a strong E presence for their online classes? This volume highlights the need for creating a presence in the online environment. The authors explore the emotional, psychological, and social aspects from both the instructor and student perspective. It provides an instructional design framework and shows how a strong presence contributes to effective teaching and learning. Filled with illustrative examples and based on research and experience, the book contains methods, case scenarios, and activities for creating, maintaining, and evaluating presence throughout the cycle of an online course.'--
Includes bibliographical references and index
Keywords: Web-based instruction -- Social aspects; Distance education -- Social aspects; Education, Higher -- Computer-assisted instruction; Human-computer interaction; Emotions and cognition